2003
DOI: 10.1038/nn1121
|View full text |Cite|
|
Sign up to set email alerts
|

Expert face processing requires visual input to the right hemisphere during infancy

Abstract: Adult expertise in face processing is mediated largely by neural networks in the right hemisphere. Here we evaluate the contribution of early visual input in establishing this neural substrate. We compared visually normal individuals to patients for whom visual input had been restricted mainly to one hemisphere during infancy. We show that early deprivation of visual input to the right hemisphere severely impairs the development of expert face processing, whereas deprivation restricted mainly to the left hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
174
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(205 citation statements)
references
References 31 publications
28
174
1
2
Order By: Relevance
“…But it is possible that the social deficit and the perceptual disorder work in tandem: the lack of experience and the inadequate attention to faces may limit the acquisition of the normal configural perceptual skill. Consistent with the claim that expertise comes to fine-tune or optimize the fusiform gyrus (FG), the putative 'face area', as a function of experience with a class of stimuli (Gauthier et al, submitted for publicationGauthier, Tarr, Anderson, Skudlarski, & Gore, 1999;Le Grand, Mondloch, Maurer, & Brent, 2003), the fusiform region of autistic individuals does not apparently come to respond preferentially to faces and this hypoactivation may be a direct reflection of the social disability (Schultz, 2005;Schultz et al, 2003). Some, although not all, recent functional magnetic resonance imaging studies have shown reduced activation of the FG of autistic individuals when viewing faces; instead strong activation is noted in the inferior temporal gyrus region, the region activated during object discrimination in controls (Grelotti et al, 2005;Hubl et al, 2003;Pierce et al, 2004Pierce et al, , 2001Schultz et al, 2000).…”
Section: Preference For Local Information In Autismmentioning
confidence: 89%
“…But it is possible that the social deficit and the perceptual disorder work in tandem: the lack of experience and the inadequate attention to faces may limit the acquisition of the normal configural perceptual skill. Consistent with the claim that expertise comes to fine-tune or optimize the fusiform gyrus (FG), the putative 'face area', as a function of experience with a class of stimuli (Gauthier et al, submitted for publicationGauthier, Tarr, Anderson, Skudlarski, & Gore, 1999;Le Grand, Mondloch, Maurer, & Brent, 2003), the fusiform region of autistic individuals does not apparently come to respond preferentially to faces and this hypoactivation may be a direct reflection of the social disability (Schultz, 2005;Schultz et al, 2003). Some, although not all, recent functional magnetic resonance imaging studies have shown reduced activation of the FG of autistic individuals when viewing faces; instead strong activation is noted in the inferior temporal gyrus region, the region activated during object discrimination in controls (Grelotti et al, 2005;Hubl et al, 2003;Pierce et al, 2004Pierce et al, , 2001Schultz et al, 2000).…”
Section: Preference For Local Information In Autismmentioning
confidence: 89%
“…Thus, pattern vision in the first few months of life is necessary for the development of normal face processing as an adult; years of subsequent visual experience with faces is not sufficient. Most intriguingly, it is early deprivation of input specifically to the right hemisphere that leads to adult impairments in face processing in these individuals; early deprivation of visual input to the left hemisphere does not (Le Grand et al 2003). Thus, although these investigations point to a critical role of experience in the construction or maintenance of face-processing mechanisms, this experience must be directed to a specific anatomical target (the right hemisphere) and must occur very early in development.…”
Section: Open Questionsmentioning
confidence: 99%
“…The trial order was randomised within orientation blocks (part-whole) but the block order was fixed (orientation). In fixing the block order, we followed previous studies that have begun with upright face trials to maximise the ecological validity of the face recognition task, and blocked orientation to allow children to develop recognition strategies for each orientation (e.g., LeGrand et al, 2003;Mondloch et al, 2002;Yovel & Kanwisher, in press). A fixed order of blocks risks confounding orientation effects with order effects in the results, for example, if there is poorer performance on later blocks through tiredness.…”
Section: Try To Answer As Fast As Possible"mentioning
confidence: 99%